E-Commerce Di Era Industri 4.0 Dan Society 5.0 - Decky Hendarsyah (LPPM ISNJ Bengkalis, 2019)
This paper discusses e-commerce, industry 4.0 and society 5.0 which includes definitions, history, framework and dimensions of technology. From this scope, a comparison was made between industry 4.0 and society 5.0 and a discussion on the alignment and impact of industry 4.0 and society 5.0 on e-commerce. After a deeper comparison and discussion, it can be concluded that technology society 5.0 is a continuation of industry technology 4.0. Then there is technology alignment between e-commerce with the era of industrial 4.0 and society 5.0, where e-commerce technology follows and adapts its technology to each of those eras. The era of industrial 4.0 and society 5.0 had many positive impacts on the development and progress of e-commerce.